Alcohol dependence decreases functional activation of the caudate nucleus during model-based decision processes - Magrabi, Amadeus; Beck, Anne; Schad, Daniel; Lett, Tristram A.; Stoppel, Christian; Charlet, Katrin; Kiefer, Falk; Heinz, Andreas; Walter, Henrik (Alcoholism, 2022)
Background Impaired decision making, a key characteristic of alcohol dependence (AD), manifests in continuous alcohol consumption despite severe negative consequences. The neural basis of this impairment in individuals with AD and differences with known neural decision mechanisms among healthy subjects are not fully understood. In particular, it is unclear whether the choice behavior among individuals with AD is based on a general impairment of decision mechanisms or is mainly explained by altered value attribution, with an overly high subjective value attributed to alcohol-related stimuli. Methods Here, we use a functional magnetic resonance imaging (fMRI) monetary reward task to compare the neural processes of model-based decision making and value computation between AD individuals (n = 32) and healthy controls (n = 32). During fMRI, participants evaluated monetary offers with respect to dynamically changing constraints and different levels of uncertainty. Results Individuals with AD showed lower activation associated with model-based decision processes in the caudate nucleus than controls, but there were no group differences in value-related neural activity or task performance. Conclusions Our findings highlight the role of the caudate nucleus in impaired model-based decisions of alcohol-dependent individuals.